Isolated medial meniscal tear in a Border Collie - Ridge, P. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
A three-year-old, female Border Collie was successfully treated for an isolated, torn, medial meniscus by arthroscopic meniscal tear resection. The dog returned to agility competition without recurrence of lameness.
Keywords: Canine; meniscal tear